2023
DOI: 10.1111/ppl.14029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil moisture stress during the silk emergence and grain‐filling in maize

Ranadheer Reddy Vennam,
Sadikshya Poudel,
Purushothaman Ramamoorthy
et al.

Abstract: Suboptimal soil moisture during the growing season often limits maize growth and yield. However, the growth stage‐specific responses of maize to soil moisture regimes have not been thoroughly investigated. This study investigated the response of maize to five different soil moisture regimes, that are, 0.25, 0.20, 0.15, 0.10, and 0.05 m3 m−3 volumetric water content (VWC), during flowering and grain‐filling stages. Sub‐optimal soil moisture at the flowering and grain‐filling stages reduced ear leaf stomatal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…As an adaptive strategy (differential transpiration) under interactive heat and drought, plants close leaf stomata while flower and pod stomata remain open (Cohen et al, 2021b; Sinha et al, 2022). Whereas comparatively higher transpiration was observed in the reproductive tissue than the vegetative as a protective mechanism to avoid overheating (Sinha et al, 2022; Vennam et al, 2023a). The canopy temperature, an integrative trait that reflects the plant water status, increased by 8 °C under combined stress had a pronounced disruption of photosynthesis and stomatal conductance, consistent with previous study (Cohen et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…As an adaptive strategy (differential transpiration) under interactive heat and drought, plants close leaf stomata while flower and pod stomata remain open (Cohen et al, 2021b; Sinha et al, 2022). Whereas comparatively higher transpiration was observed in the reproductive tissue than the vegetative as a protective mechanism to avoid overheating (Sinha et al, 2022; Vennam et al, 2023a). The canopy temperature, an integrative trait that reflects the plant water status, increased by 8 °C under combined stress had a pronounced disruption of photosynthesis and stomatal conductance, consistent with previous study (Cohen et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, not all growth stages have an equal impact on crop yield. For instance, in maize cultivation, the silking stage is highly sensitive to water stress, necessitating meticulous irrigation management [51,52]. Additionally, the V5 and jointing stages, when the stem of maize grows fast described in Table 1, demand increased attention due to maize's heightened need for nitrogen fertilizer and water during these phases [53][54][55][56][57].…”
Section: Harvest (Hv)mentioning
confidence: 99%
“…Kukal and Irmak [9] reported that corn had the greatest irrigation-limited yield gap globally among the major rainfed crops, with an increase of 2.7 times in yield under irrigated conditions. During critical growth stages, moisture stress severely affects corn plant growth and development, resulting in reduced plant stand, reproductive failure, and yield [10].…”
Section: Introductionmentioning
confidence: 99%